Long-Term Follow-Up of Outcomes With F-18-Fluorodeoxyglucose Positron Emission Tomography Imaging–Assisted Management of Patients With Severe Left Ventricular Dysfunction Secondary to Coronary Disease. (September 2016) - Mc Ardle, Brian; Shukla, Tushar; Nichol, Graham; deKemp, Robert A.; Bernick, Jordan; Guo, Ann; Lim, Siok Ping; Davies, Ross A.; Haddad, Haissam; Duchesne, Lloyd; Hendry, Paul; Masters, Roy; et al.
Abstract : Background—: Whether viability imaging can impact long-term patient outcomes is uncertain. The PARR-2 study (Positron Emission Tomography and Recovery Following Revascularization) showed a nonsignificant trend toward improved outcomes at 1 year using an F-18-fluorodeoxyglucose positron emission tomography (PET)–assisted strategy in patients with suspected ischemic cardiomyopathy. When patients adhered to F-18-fluorodeoxyglucose PET recommendations, outcome benefit was observed. Long-term outcomes of viability imaging–assisted management have not previously been evaluated in a randomized controlled trial. Methods and Results—: PARR-2 randomized patients with severe left ventricular dysfunction and suspected CAD being considered for revascularization or transplantation to standard care (n= 195) versus PET-assisted management (n=197) at sites participating in long-term follow-up. The predefined primary outcome was time to composite event (cardiac death, myocardial infarction, or cardiac hospitalization). After 5 years, 105 (53%) patients in the PET arm and 111 (57%) in the standard care arm experienced the composite event (hazard ratio for time to composite event =0.82 [95% confidence interval 0.62–1.07]; P =0.15). When only patients who adhered to PET recommendations were included, the hazard ratio for the time to primary outcome was 0.73 (95% confidence interval 0.54–0.99; P =0.042). Conclusions—: After a 5-year follow-up in patients with left ventricular dysfunction and suspected CAD, overall, PET-assisted management did not significantly reduce cardiac events compared with standard care. However, significant benefits were observed when there was adherence to PET recommendations. PET viability imaging may be best applied when there is likely to be adherence to imaging-based recommendations. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00385242. Abstract : Supplemental Digital Content is available in the text.